Critical Approaches in the Design of a Mobile Phone Diet Application For Prolong Use (International Journal of Innovative Computing, 2013)
This Many mobile phone diet applications are available today, most of which are free for the user to download on their mobile phone. However, findings have reported that, the existing applications for diet management are not very effective for prolonged use. The statistics have also shown that the rate of obesity in Malaysia is increasing over time. Thus, strategies to design and develop a new mobile phone diet application must be developed. This paper reviews previous research to observe the implementation of diet management elements in existing mobile phone applications. The aim of this review is to improve current mobile phone diet application development efforts towards effective diet management in terms of prolonged usage by identifying the effective approaches from previous research. This paper not only includes a review of relevant journal papers but also a review of the various available online diet management systems. This approach is used to identify the current trends in the implementation of mobile phone diet applications. The main finding of this review is a conceptual model that consists of an important approach to the design of mobile applications for diet management developed so that users will use the application long-term. Additionally it is hoped that the conceptual model will prove helpful for health practitioners or mobile application developers in the development of an effective mobile diet application for successful long-term diet maintenance. Ideally, our approach will aid in overcoming obesity, which is a well-known disease in many countries today.